Vancomycine determination in serum – comparison of methods - Ljubenović, Milanka; Ćosić, Vladan; Stojiljković, Vladana; Milosavljević, Biljana; Simić, Jovana; Vujović, Maja; Kostić, Emilija; Ljubenović, Bojan (Archives of Pharmacy, 2022)
Vancomycin is a glycopeptide antibiotic used in the treatment of infections caused by numerous gram-positive bacteria, primarily Staphylococcus aureus, and in patients without a therapeutic response to penicillin and cephalosporins. Therapeutic serum vancomycin concentrations are 5-10 mg/L. Higher concentrations ​​can cause serious adverse reactions such as ototoxicity and nephrotoxicity, therefore monitoring of serum vancomycin levels is essential. The aim of the paper is comparison of the results obtained by immunoenzyme assay and chromatographic method. Vancomycine was quantified in 36 serum samples using immuno enzyme essay (Emit 2000 Vancomycin Assay test), with Beckman Coulter Analyzer system and Shimadzu ultrafast liquid chromatographer with triple-quadrupole mass spectrometer (LCMS-8030). The results were statistically analyzed using SPSS 20. Samples for hromatographic analyses were prepared by protein precipitation and separation was performed on the column Kinetex C18, 1,7um, 50 x 2.1mm, termostated on 50, using mobile phase consisted of 0.1% formic acid in water (A) and 0.1% formic acid in acetonitrile (B), with 0.45 mL/min gradient flow rate. Vancomycine MRM transition in ESI (+) mode is 725.2>144. Using the student's t test, it was shown that there is no statistical difference in the results obtained by two described methods (p=0.069 ≥ 0.05). The correlation coefficient of the obtained results is r=0.9972. According to the obtained results, immunoassay and chromatographic methods are reliable and are applicable to routine vancomycine monitoring.